Experimental and finite element analysis of tubular conveyor gallery - Gopinath, M.; Senthil, R. (Journal of Structural Engineering, 2024)
A conveyor system is a continuous system for haulage of the bulk materials. It enables us to haul anything from corn to iron ore in a continuous flow from one end of the plant to the other, feeding and reclaiming material through the different stages of the process. The tubular conveyor galleries consist of a tube, shop fabricated using steel plates forged to the required radius and welded at the longitudinal and circumferential joint section in a staggered pattern. This paper presents details of the finite element analysis (FEA) carried out to understand the behaviour of the tubular conveyer gallery systems subjected to concentrated load due to conveyer supporting system subjected to biaxial bending. Studies carried out to obtain the optimum size of the openings that can be provided for lighting and ventilation without affecting the stability of the structure to withstand dynamic loads are explained. Details of experimental investigations carried out on the scaled down model of the tubular conveyor gallery to compare the results of FEA is also presented in this paper.